Recent advances of sorafenib nanoformulations for cancer therapy: Smart nanosystem and combination therapy - Fangmin Chen; Yifan Fang; Xiang Chen; Rui Deng; Yongjie Zhang; Jingwei Shao (Elsevier, 2021)
Sorafenib, a molecular targeted multi-kinase inhibitor, has received considerable interests in recent years due to its significant profiles of efficacy in cancer therapy. However, poor pharmacokinetic properties such as limited water solubility, rapid elimination and metabolism lead to low bioavailability, restricting its further clinical application. Over the past decade, with substantial progress achieved in the development of nanotechnology, various types of smart sorafenib nanoformulations have been developed to improve the targetability as well as the bioavailability of sorafenib. In this review, we summarize various aspects from the preparation and characterization to the evaluation of antitumor efficacy of numerous stimuli-responsive sorafenib nanodelivery systems, particularly with emphasis on their mechanism of drug release and tumor microenvironment response. In addition, this review makes great effort to summarize the nanosystem-based combination therapy of sorafenib with other antitumor agents, which can provide detailed information for further synergistic cancer therapy. In the final section of this review, we also provide a detailed discussion of future challenges and prospects of designing and developing ideal sorafenib nanoformulations for clinical cancer therapy.